Compensation and exotic livestock disease management: the views of animal keepers and veterinarians in England. (19th November 2016) - Hamilton‐Webb, A.; Naylor, R.; Little, R.; Maye, D.
Abstract : Relatively little is known about the perceived influence of different compensation systems on animal keepers' management of exotic livestock disease. This paper aims to address this research gap by drawing on interviews with 61 animal keepers and 21 veterinarians, as well as a series of nine animal keeper focus groups across five different livestock sectors in England. The perceived influence of current compensation systems on disease control behaviour was explored and alternative compensation systems that respectively reward positive practices and penalise poor practices were presented in the form of scenarios, alongside a third system that considered the option of a cost‐sharing levy system between industry and government. The results indicate that animal keepers consider themselves to be influenced by a range of non‐financial factors, for example, feelings of responsibility, reputation and animal welfare concerns, in the context of their exotic disease management practices. The majority of animal keepers were unaware of the current compensation systems in place for exotic diseases, and were therefore not consciously influenced by financial recompense. Concerns were raised about linking compensation to disease management behaviour due to auditing difficulties. A cost‐sharing levy system would likely raise awareness of exotic disease and compensation among animal keepers, but differentiation of payments based upon individual farm‐level risk assessments was called for by participants as a strategy to promote positive disease management practices.